Pembinaan disiplin dilingkungan masyarakat kota Denpasar - Arsana, I Gusti Ketut Gde.; Kusuma, Made Supartha Endra.; Indonesia. (Departemen Pendidikan dan Kebudayaan, Direktorat Jenderal Kebudayaan, Direktorat Sejarah dan Nilai Tradisional, Proyek Penelitian, Pengkajian dan Pembinaan Nilai-Nilai Budaya Bali, 1995)
Discipline among the people of the city of Denpasar, Bali Province.
Includes bibliographical references (p. 175-177).
Discipline among the people of the city of Denpasar, Bali Province.
Keywords: Community life / Indonesia / Denpasar.; Discipline. / http://id.loc.gov/authorities/subjects/sh85038329; Denpasar (Indonesia) / Social conditions.